The influence of perceived quality and perceived price towards the purchase intention of kebaya product: perspective of female students in college - Ali Fikri, Ramadhan; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2019)
Indonesia have been roused by social legacy which reflected through nearby conventional clothes and fabrics in fashion industry such as kebaya. Kebaya is one of kind cultural heritage products in the fashion industry has a high value and uniqueness. However, as entrepreneurs create kebaya product, SVAN Company has difficulties to fit the target market which is female students in college. Therefore, this research is conducted to understand the dimension of perceived quality and perceived price towards female students in college purchase intention. Data gather from around 225 respondents, by purposive sampling method with requirements for female students in college for diploma and bachelor, attain the age of 17 years old or above, and currently living in Banten, DKI Jakarta, and West Java Province also income no more than Rp 3.000.000. Multiple Linear Regression Analysis is also used to process the data. As a result, perceived quality and perceived price have significant influence towards female students in college purchase intention simultaneously for kebaya product, which the independent variables could explain more than 40% of the dependent variable.Keywords: perceived quality, perceived price, kebaya, female students in college, purchase intention